(untitled) (Research, Society and Development, 2022)
Introduction: In front of the actual context of protagonism return of clinic use of 3,4-Methylenedioxymethamphetamine (MDMA) after years of research stoppage with psychedelics, it has emerged several studies with the objective of finding an effective alternative for Post Traumatic Stress Disorder (PTSD) treatment with the assistance of psychotherapy.Objectives: The present study has the objective of bringing information about the actual and contextualized scenery of MDMA research in the PTSD treatment as the effective avaliation in front of the view of recent and relevant randomized clinical trials studies.Methodology: PRISMA was used as protocol and the data base consulted was: Pubmed, Embase, Scopus and Biblioteca Virtual em Saúde. The Periodic CAPES was the platform used to get access of full texts in some cases. The eligibility criteria included only double-blind randomized controlled trials with MDMA utilization for PTSD treatment in English language.Results: Five studies were included in Systematic Review, with the content of 176 patients with mean age: 37 to 42 years old. The predominant country in the studies was the United States, but also appears: Canada, Israel and Switzerland. The compilation of studies was considered homogeneous in terms of utilized intervention, research methodology and patients. Conclusion: With the data, exposed literature, and considering an impartial vision about psychedelics, it is possible to conclude that 3,4-Methylenedioxymethamphetamine holds a tremendous potential that can be even more explored in reference to PTSD treatment.